Effects of massotherapy on autistic children - Oliveira, Jéssica Masi de; Amorese, Roberta Chaves Penco; Santos, Franciele Cruz Rocker (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 39 No especial (2023): Estética e Cosmética, 2023)
Autism is a deficiency in bioneurological development, which affects the central nervous system in the areas of social interaction, communication skills and cognitive function. autistics have normal physical development. But they have great difficulty in establishing social or affective relationships and show signs of living in an isolated world. The causes of autism are not fully known. The relaxing effect caused by massage can alter the behavior of autistic children, in addition, it encourages the child to get used to touch and relationships with other people. This article sought scientific data on the function and effects of massage therapy in the aforementioned pathology, as well as on the basic structure of the skin. However, further research is needed regarding the benefits of massage therapy in autism treatment.